2016
DOI: 10.2139/ssrn.2877136
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Performing Arts: The Effect of Unobserved Quality on Price Elasticity

Abstract: This paper studies behavior patterns among theater attendees in the process of ticket purchasing. Since the theater attempts to balance between a high occupancy and affordable prices, the purpose of the study is to reveal the effects of changes in prices on attendance. This project is conducted conjointly with the Perm Tchaikovsky Opera and Ballet Theater. Data are taken from the sales information system of the theater for four seasons 2011-2012/2014-2015. The data are disaggregated to the level of the seating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…types of live events (e.g., concerts, performing arts) (e.g., Zieba, 2009;Felton, 1992;Pompe et al, 2018;Buzanakova and Ozhegov, 2016). In order to check that this also holds in our setting, we surveyed the prices of live content on Zhihu and competing platforms in China during 2016-2017, by randomly scarping about 100 paid content/events from each platform.…”
Section: Resultsmentioning
confidence: 99%
“…types of live events (e.g., concerts, performing arts) (e.g., Zieba, 2009;Felton, 1992;Pompe et al, 2018;Buzanakova and Ozhegov, 2016). In order to check that this also holds in our setting, we surveyed the prices of live content on Zhihu and competing platforms in China during 2016-2017, by randomly scarping about 100 paid content/events from each platform.…”
Section: Resultsmentioning
confidence: 99%
“…Schimmelpfennig [ 16 ] concluded that there exist opportunities in some locations for price cuts for increased both attendance and revenue. That was the case for the rear part of the Amphitheatre in which it could be possible to increase -differently- the median attendance for two different ballet performances [ 16 ] In the theatrical industry, demand elasticities vary within seating categories [ 17 ]. The distance from the front in theaters plays a crucial role in identifying the optimal number of high-price seating rows.…”
Section: Introductionmentioning
confidence: 99%